2017
DOI: 10.1055/s-0043-122237
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Basal Serum Calcitonin for the Diagnosis of Medullary Thyroid Cancer

Abstract: Calcitonin (CT), a tumor marker for medullary thyroid cancer (MTC), can be stimulated with pentagastrin or calcium. Because of the unavailability of pentagastrin, basal CT measurement is frequently used for the preoperative diagnosis of MTC. The aim of the study was to define basal serum calcitonin (bCT) cut-off thresholds for diagnosing MTC. Within a retrospective analysis, 114 patients (51 males) were included fulfilling the criteria of an increased preoperative bCT level (>10 pg/ml) and the criteria of an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
14
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 39 publications
4
14
0
6
Order By: Relevance
“…60 pg/mL in men. These cut-offs were measured by using the newer calcitonin assays and were also confirmed by other working groups (3,4). This means a grey area for calcitonin of 20-30 pg/mL in women and 30-60 pg/mL in men, where 6-13% of smaller MTC were missed, but C-cell hyperplasia was diagnosed just as often.…”
supporting
confidence: 59%
“…60 pg/mL in men. These cut-offs were measured by using the newer calcitonin assays and were also confirmed by other working groups (3,4). This means a grey area for calcitonin of 20-30 pg/mL in women and 30-60 pg/mL in men, where 6-13% of smaller MTC were missed, but C-cell hyperplasia was diagnosed just as often.…”
supporting
confidence: 59%
“…There is a possibility of false positive elevated calcitonin levels, and recent studies have evaluated the basal serum calcitonin cut-off thresholds for diagnosing MTC. Allelein et al (258) found that the most precise basal calcitonin thresholds for the identification of MTC were ≥ 10. wide grey-zones, and most importantly, if healing is to be achieved, the thyroidectomy must be performed before metastatic lymph nodes occur.…”
Section: Diagnostic Centers -Calcitonin Screeningmentioning
confidence: 99%
“…In the present study, using the reference range of the assay or adopting the traditional cut offs of 10, 15, or 20 pg/ml, only 16, 12, 5, and 3 patients, respectively, would require additional investigation without compromising the detection of the two cases of MTC. Thus, the adoption of a higher cut off such as 15 pg/ml [24,25] or 20 pg/ml [26][27][28] for basal Ctn would markedly reduce the number of false-positive cases and the need for additional investigation, without or only slightly affecting sensitivity. In the few patients who will still require additional investigation, stimulated Ctn (using calcium if pentagastrin is not available) and/ or FNA-Ctn could be obtained [19].…”
Section: Discussionmentioning
confidence: 99%